Therapeutic Effect of Red Spinach (Amaranthus tricolor L.) Extract on Pancreatic MDA Levels Rats (Rattus norvegicus) Exposed to MLD-STZ - Kartika Rahma; Ois Nurcahyanti (Journal of Biomedicine and Translational Research, 2021)
Background: Several studies have reported that an increase in blood glucose in patients with diabetes mellitus (DM) can cause complications to death that occur due to oxidative stress conditions due to excessive ROS production. Red spinach extract was found to be rich in antioxidant compounds. However, there has been no further research on the ability of red spinach to lower blood glucose levels and prevent oxidative stress, which can be seen from the levels of malondialdehyde (MDA; a marker of oxidative stress) in the DM body.Objective: This study aims to determine whether there is a change in blood glucose levels and MDA levels in DM animal models between the groups that were given red spinach extract and not.Methods: This study used white rats (Rattus norvegicus) which were divided into 5 groups: K(-) group in which the rats were not induced by diabetogenic agent and were not treated; K(+) group, the rats were made DM induced by multiple low dose streptozotocin (MLD-STZ); and T1, T2, and T3 groups were exposed to MLD-STZ and treated with red spinach extract (Amaranthus tricolor L.) at a dose of 200 mg/kgBW, 300 mg/kgBW and 400 mg/kgBW, respectively. Blood sugar levels were checked before and after treatment with extract using glucometer digital. Meanwhile, MDA levels were measured by TBA test using protein isolates from the pancreas of each rat.Results: The results showed that the average MDA levels in the K-, K+, T1, T2, and T3 groups were 1.759±0.08, 2.280±0.15, 2.303±0.11, 1.927±0.06, and 1.801±0.04. While the average blood sugar levels in the K-, K+, T1, T2, and T3 groups were 114.4±8.82, 464±72.78, 421.2±37.60, 140.6±20.19, and 176±13.06.Conclusion: It can be concluded that the administration of red spinach extract therapy in DM model rats was able to reduce both glucose levels and MDA levels. By lowering the levels of MDA compounds, it is also believed to be able to prevent oxidative stress in cells which causes tissue damage.